Mengarungi Gelombang Digital: Peran Self-compassion dan Gratitude Terhadap Online FoMO Pada Mahasiswa - Hanifah, Raidah; Saikhoni, Saikhoni; Wigati, Meilia; Wilantika, Rima; Syaifussalam, Muhammad Lathief (Universitas Muria Kudus, 2024)
This research aims to determine the role of self-compassion and gratitude on online FoMO in students. Testing the hypothesis in this research uses multiple linear regression analysis. The subjects in this research were 257 students in Lampung, Indonesia. Partially, in this research, the results showed that there was a very significant role between self-compassion and online FoMO, p = 0.007 and t value of -2.272. The partial test of the second hypothesis resulted in a very significant role between gratitude towards online FoMO p = 0.004 with a t value of -2.931. Based on the multiple linear regression test, the results showed that there was a very significant role between self-compassion and gratitude on online FoMO in students (F = 10.916, significance 0.000 p0.001). This means that the higher the compassion and gratitude, the lower the online FoMO and vice versa. The contribution of the effective variable self-compassion to online FoMO was 7.6% and the effective contribution of gratitude to online FoMO was 10.1%.Penelitian ini bertujuan untuk mengetahui peran antara self-compassion dan gratitude terhadap online FoMO pada mahasiswa. Menguji hipotesis pada penelitian ini menggunakan analisis regresi linear berganda. Subjek pada penelitian ini merupakan mahasiswa di Lampung, Indonesia sebanyak 257 mahasiswa. Secara partial pada penelitian ini didapatkan hasil bahwa terdapat peran yang sangat signifikan antara self-compassion terhadap online FoMO p = 0.007 dan nilai t -2,272. Uji partial hipotesis kedua dengan hasil terdapat peran yang sangat signifikan antara gratitude terhadap online FoMO p = 0.004 dengan nilai t -2.931. Berdasarkan uji regresi linear berganda didapatkan hasil terdapat peran yang sangat signifikan antara self-compassion dan gratitude terhadap online FoMO pada mahasiswa (F = 10,916 signifikansi 0,000 p0,001). Artinya, semakin tinggi self-compassion dan gratitude maka akan semakin rendah online FoMO dan sebaliknya. Sumbangan efektif variable self-compassion terhadap online FoMO sebesar 7,6% dan sumbangan efektif gratitude terhadap online FoMO sebesar 10,1%.